An Efficient Synthesis of 1,5-Benzodiazepines Using AlCl3 Under Solvent Free Condition - B. More, Uttam; S. Kharat, Ramdas; P. Mahulikar, Pramod (Asian Journal of Chemistry, 2011)
A mild, efficient and rapid method for synthesis of 1,5-benzodiazepines from o-phenylenediamine and different ketones has been developed by using aluminium chloride as a catalyst. The higher yield and purity of products is additional feature of the methodology.